Islamic Banking Regulation In Indonesia: A Review Of Laws, OJK Regulations (POJK), and DSN-MUI Fatwas - Ichsanul Reihan Adel; Nurnasrina (JAWI : Journal of Ahkam Wa Iqtishad, 2026)
The development of Islamic banking in Indonesia is inseparable from the existence of a legal framework governing its operations and supervision. Islamic banking regulations are derived from various legal instruments, such as the Islamic Banking Law, regulations issued by the Financial Services Authority (Peraturan Otoritas Jasa Keuangan/POJK), and fatwas of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). Although originating from different authorities, these three legal instruments are closely interconnected in shaping an Islamic banking system that is consistent with Sharia principles and Indonesia’s positive law. This study aims to analyze the roles, legal standing, and implications of Law No. 21 of 2008, POJK, and DSN-MUI fatwas within the regulatory structure of Islamic banking in Indonesia. The research employs a normative juridical method with statutory and conceptual approaches. The findings indicate that Islamic banking regulation in Indonesia represents an integration of state law and Islamic law, harmonized through authoritative mechanisms.